Weight bias internalization and its association with psychological distress and weight-related factors among youths in university, Thailand - Suneerat Yangyuen; Thidarat Somdee; Meihua Yin; Atchara Chaichan (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Weight bias internalization (WBI) is associated with poor weight-related health and psychological health problems in adults. However, less is known about WBI in Thai youths, and its associated factors are scarce. This study aimed to assess the association between psychological, weight-related factors, and WBI among Thai youths. MATERIALS AND METHODS: A cross-sectional design was conducted on 1185 university youths from three universities in northeastern, Thailand from January to June 2023, with multistage sampling methods. The data were collected by self-administered questionnaire. Multinomial logistic regression was applied to explore factors that influence WBI. RESULTS: Most of the youth were female; with the average body mass index (BMI) was 23.3 ± 3.2 kg/m2. More than half (n = 628; 52.9%) of them reported a high level of WBI that was present across the weight spectrum. Approximately 41.4% (n = 490) reported being dissatisfied with their body image, and 50.6% (n = 600) had peers with obesity. WBI was positively related to depressive symptoms, perceived stress, the experience of weight stigma, BMI, and body image dissatisfaction. Conversely, it was negatively related to self-esteem and peers with obesity. CONCLUSION: WBI is influenced by several psychological and weight-related factors. Additionally, youths across body weight categories could be vulnerable to high WBI. Hence, consideration of these potential factors could be useful in designing targeted interventions to reduce WBI.